1995
DOI: 10.1016/0092-8674(95)90162-0
|View full text |Cite
|
Sign up to set email alerts
|

Divergent seven transmembrane receptors are candidate chemosensory receptors in C. elegans

Abstract: Using their senses of taste and smell, animals recognize a wide variety of chemicals. The nematode C. elegans has only fourteen types of chemosensory neurons, but it responds to dozens of chemicals, because each chemosensory neuron detects several stimuli. Here we describe over 40 highly divergent members of the G protein-coupled receptor family that could contribute to this functional diversity. Most of these candidate receptor genes are in clusters of two to nine similar genes. Eleven of fourteen tested gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
571
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 645 publications
(591 citation statements)
references
References 43 publications
14
571
0
1
Order By: Relevance
“…This gene is only expressed by AWA neurons, two of the 32 chemosensory neurons in C. elegans. More than 40 highly divergent members of this family of G-protein-coupled receptor in the C. elegans have been identified (39). Eleven of 14 tested receptor genes appear to be expressed in chemosensory neurons, but as observed in vertebrates, three of them are expressed in nonsensory cells.…”
Section: Discussionmentioning
confidence: 99%
“…This gene is only expressed by AWA neurons, two of the 32 chemosensory neurons in C. elegans. More than 40 highly divergent members of this family of G-protein-coupled receptor in the C. elegans have been identified (39). Eleven of 14 tested receptor genes appear to be expressed in chemosensory neurons, but as observed in vertebrates, three of them are expressed in nonsensory cells.…”
Section: Discussionmentioning
confidence: 99%
“…Their gene structure contrasts sharply, however, with that of vertebrate ORs; their exons are interspersed among multiple introns (e.g., Robertson, 2000), and they show little sequence similarity with vertebrate olfactory receptors (Troemel et al, 1995;Sengupta et al, 1996;Clyne et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…1e), which is required for ASH-mediated avoidance of bitter tastes 8 . It has been reported that high concentrations of volatile repellents are also detected by ASH neurons 5 . OSM-9, the worm homologue of the vertebrate nociceptive channel TRPV1 (the capsaicin receptor), generally participates in perception of repellents by ASH neurons 12,13 .…”
mentioning
confidence: 99%